Study on Seismic Analysis of Multi Storey RCC Frame With and Without Shear Wall Using NBC 105:2020 (International Journal of Innovative Research in Engineering & Management, 2022)
The aftermath of an earthquake manifests  great devastation due to unpredicted seismic motion  striking extensive damage to innumerable buildings of  varying degree, i.e. either  full or partial. This damage to structures in turn causes  irreparable loss of life with a large number of casualties.  Strengthening of structures proves to be a better option  catering to the economic considerations and immediate  shelter problems rather than replacement of buildings.  Moreover it has been often seen that retrofitting of  buildings is generally more economical as compared to  demolition and reconstruction. Therefore, seismic  retrofitting or strengthening of building structures is one of  the most important aspects for mitigation seismic hazards  especially in earthquake prone areas. Seismic strengthening  or retrofitting is generally carried out in two ways either  global retrofit methods or local retrofit methods. In this  study, the seismic performance of reinforced concrete (RC)  buildings with shear walls is studied. The effect of shear  walls on lateral capacity of the building has been examined.  For this purpose RC building with and without shear walls  has been analyzed. The performance of the building is  evaluated using parameters such as time period, lateral  displacement, base shear and storey drift. It is observed  from the present study that the shear wall system improves  not only the lateral stiffness and strength capacity but also  the displacement capacity of the structure. The seismic  performance of the frame also depends upon location of  shear walls and its symmetry. Hence, addition of shear  walls in existing buildings is an effective tool for seismic  strengthening like the other methods of retrofitting. In this project attempt is made to understand the Seismic  performance of building with shear wall and without shear  wall. The main objective of this project is to find out which  will have better seismic performance either building with  shear wall or building without shear wall. In present study  RCC building models having G+9 stories with shear wall  and without shear walls considered for analysis. The  analysis of model is done using equivalent static method in  ETABS software. Finally the results of seismic behavior of  buildings are compared with respect to time period, base  shear, storey shear, member forces, overturning moment,  displacement, stiffness and drifts.
Keywords: Displacement; Stiffness; Base Shear; Storey Drift